Orchestrating NK and T cells via tri-specific nano-antibodies for synergistic antitumor immunity - Qian-Ni Ye; Long Zhu; Jie Liang; Dong-Kun Zhao; Tai-Yu Tian; Ya-Nan Fan; Si-Yi Ye; Hua Liu; Xiao-Yi Huang; Zhi-Ting Cao; Song Shen; Jun Wang (Nature Communications, 2024)
Abstract The functions of natural killer (NK) and T cells in innate and adaptive immunity, as well as their functions in tumor eradication, are complementary and intertwined. Here we show that utilization of multi-specific antibodies or nano-antibodies capable of simultaneously targeting both NK and T cells could be a valuable approach in cancer immunotherapy. Here, we introduce a tri-specific Nano-Antibody (Tri-NAb), generated by immobilizing three types of monoclonal antibodies (mAbs), using an optimized albumin/polyester composite nanoparticle conjugated with anti-Fc antibody. This Tri-NAb, targeting PDL1, 4-1BB, and NKG2A (or TIGIT) simultaneously, effectively binds to NK and CD8+ T cells, triggering their activation and proliferation, while facilitating their interaction with tumor cells, thereby inducing efficient tumor killing. Importantly, the antitumor efficacy of Tri-NAb is validated in multiple models, including patient-derived tumor organoids and humanized mice, highlighting the translational potential of NK and T cell co-targeting.